Unity Of All Religions: The Gandhian way (Sarva Dharma Samabhava) - Sreenivasulu Naik, B (Mittal Publications, 2018)
This book constitutes both, a comprehensive discussion of Gandhian religious beliefs for new comers to the subject and a clear and useful reference for those who need to an accurate description and understanding of different religions.